2017
DOI: 10.1039/c6sc01953f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intracellular telomerase activity through cascade DNA logic gates

Abstract: DNA computation allowed the imaging of intracellular telomerase and enabled the differentiation of cancer cell lines and normal cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…We finally investigated where our DNA probes were located and functioned in live cells. Costaining with 4,6‐diamino‐2‐phenylindole (DAPI) indicated that O1 and S2 were mainly distributed around the nucleus (Figure S12); thus suggesting high telomerase activity in the cytoplasm of cancer cells, which is identical to that previously reported . It is supposed that, if telomerase can trigger hairpin formation of S2 , the extended S2 will form a framework that contains multiple TTAGGG repeats.…”
Section: Resultssupporting
confidence: 77%
“…We finally investigated where our DNA probes were located and functioned in live cells. Costaining with 4,6‐diamino‐2‐phenylindole (DAPI) indicated that O1 and S2 were mainly distributed around the nucleus (Figure S12); thus suggesting high telomerase activity in the cytoplasm of cancer cells, which is identical to that previously reported . It is supposed that, if telomerase can trigger hairpin formation of S2 , the extended S2 will form a framework that contains multiple TTAGGG repeats.…”
Section: Resultssupporting
confidence: 77%
“…In this step, the behavior of FNA‐1 is consistent with an AND‐gate that is connected to the first OR‐gate. Taken as a whole, FNA‐1 in fact behaves as a logic circuit consisting of two cascaded logic gates (OR‐AND), of which the truth table and logic symbol are shown in Figure a (right panel) and Figure c, respectively. In contrast to FNA‐1, the control structure C‐FNA (Supporting Information, Figure S6) does not respond to external stimuli in all cases, consistent with the PAGE results.…”
Section: Resultsmentioning
confidence: 99%
“…[10,37] Since the strand-displacementr eaction can be easily cascaded and mimics the wire function in digital electronics, some logic devices werea lso developed based on the spontaneousDNA reaction. [38] Zhang and Zhu et al [39] constructed ac ascade nucleic acid logic gate that responded to intracellular telomerase and applied it in imaging intracellulart elomerase activity.T hey de-signedaDNA computation system that includes a TS probe, which is the telomerase substrate primer, at oehold-bearing DNA duplex that consists of a G T strand,afluorophore-modified G F strand and aq uencher-modified G Q strand,a nd Input B,w hich is the partial-complementary strand of G F .F irstly,t he TS probe could be extended by telomerase with repetitive sequences of TTAGGG,f orming TS + nR strand (Figure4i). The TS + nR strand could recognize and hybridize with the toehold domain of the duplex (G T -G F -G Q )t oi nitiate spontaneous strand migration and displacement,t hereby separating the flu- .…”
Section: Signals Derivedf Rom Strand-displacement Reactionsmentioning
confidence: 99%
“…Zhang and Zhu et al . constructed a cascade nucleic acid logic gate that responded to intracellular telomerase and applied it in imaging intracellular telomerase activity.…”
Section: Basic Signal Strategies Based On Dna Structuresmentioning
confidence: 99%
See 1 more Smart Citation